A combined UV-visible with fluorescence detection method based on an unlabeled aptamer and AuNPs for the sensitive detection of acetamiprid. (3rd April 2023) - Tian, Liran; Song, Xiangwei; Liu, Tianjiao; Li, Anfeng; Ning, Yang; Hua, Xiuyi; Dong, Deming; Liang, Dapeng
Abstract : A simple spectral method with a wider detection range is proposed for the detection of acetamiprid. Abstract : Based on the specific identification ability of aptamers towards a target, a combined UV-Visible with fluorescence detection method for acetamiprid was designed. In the absence of acetamiprid, AuNPs were uniformly distributed and had a good quenching ability for Rhodamine B's fluorescence at a higher NaCl concentration. In the presence of acetamiprid, a few AuNPs lost their protective effect and aggregated, meanwhile, the absorption peak of the UV-vis spectrum gradually redshifted from 520 nm to 680 nm. Additionally, the quenching effect of AuNPs on Rhodamine B was diminished when aggregation took place. Thus the presence of acetamiprid could be clearly determined using a UV-vis or fluorescence method. The combination of the two routes had a wider detection range and a detection limit as low as 0.0559 μM. This method was successfully used to determine acetamiprid in spiked lake water samples and would be a potential simple method for the determination of acetamiprid residues in natural water bodies.